Market power and heterogeneous pass-through in German electricity retail - Tomaso Duso; Florian Szücs (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
We analyze the pass-through of cost changes to retail tariffs in the German electricity market over the 2007 to 2014 period. We find an average pass-through rate of around 60%, which significantly varies with demand factors: while the pass-through rate to baseline tariffs, where firms have higher market power, is only 50%, it increases to 70% in the competitive segment of the market. Although the pass-through rate of independent firms is significantly higher than that of other firms in the competitive market segment, the extent of supply-side heterogeneity is limited. Thus, the firms' ability to exercise market power appears to be constrained by competition and largely determined by demand side factors. Finally, we find that the pass-through rate in the competitive market segment has been approaching unity over the past years, indicating a rise in competitive pressure.
Keywords: C23; D22; D43; L13; L94; Q41; 330; electricity retail; pass-through; Germany